Use of transcriptional synergy to augment sensitivity of a splicing reporter assay - Levinson, Noah (Cold Spring Harbor Laboratory Press, 2006)
A primary limitation in the development and use of screens to identify factors that regulate mammalian pre-mRNA splicing has been the development of sensitive reporter assays. Alternative splicing typically involves relatively small (< 10-fold) changes in isoform ratios. Therefore, reporter constructs designed to allow direct analysis of isoform expression historically have at most a 10-fold window of discrimination between a positive signal and background. Here we describe the design and application of a reporter cell line that makes use of the phenomenon of transcriptional synergy to amplify the detection of changes in splicing, such that a three- to five-fold change in splicing pattern is observed as a 30- to 50-fold change in GFP expression. Using this cell line we have identified two small molecules, from a library of approximately 300 synthetic compounds, that can induce partial repression of a variable exon from the CD45 gene. We propose that the concept of transcription-based amplification of signal will allow the development of true high-throughput screening approaches to identify effectors of mammalian alternative splicing.